Integrasi Pendidikan Karakter dalam Pembelajaran Al-Quran - Muspirawati, Muspirawati; Amda, Ahmad Dibul; Saputra, Hasep (JOEAI (Journal of Education and Instruction), 2021)
This study aims to observe and analyze the integration of character education in learning the Qur'an and hadith at MTsN 1 Musi Rawas Utara. This type of research is field research, while the approach used is through a qualitative approach. The qualitative approach in this study is to match the empirical reality with the applicable theory by using a descriptive method. The results of the study obtained information that the integration of character education at MTsN 1 Musi Rawas Utara was carried out by planning, implementing, and assessing. In the search results, it can be seen that all character values ​​are integrated in the lesson plan for learning Al-Quran Hadith at MTsN 1 Musi Rawas Utara, then also integrated into the learning process of Al-Quran Hadith at MTsN 1 Musi Rawas Utara by the subject teacher. In conclusion, the integration of character education in learning the Qur'an and hadith for students at MTsN 1 Musi Rawas Utara has gone through planning, implementation and assessment, and has been integrated in the lesson plan and has been implemented by subject teachers. Keywords: Learning integration, Al-Quran Hadith Learning, Character Education.